Prescribing Vitamin-K-Antagonists Versus Direct Oral Anticoagulants Among Bavarian General Practitioners: A Qualitative Study - Zeschick, Nikoletta; Gollnick, Julia; Muth, Julia; Hörbrand, Franziska; Killian, Peter; Donner-Banzhoff, Norbert; Kühlein, Thomas; Sebastiao, Maria (Health Services Insights, 2025)
Background: Direct oral anticoagulants (DOACs) have been increasingly prescribed instead of vitamin-K-antagonists (VKA) although VKAs cost considerably less than DOACs. In 2014, a new system for drug expenditures, the Wirkstoffvereinbarung (WSV, Active substance agreement), was implemented in Bavaria, Germany to control pharmaceutical expenditures transparently. Achieving the targets for the VKAs set by the WSV was difficult for general practitioners (GPs). We explored the determinants of prescribing VKAs (specifically phenprocoumon) versus DOACs. Methods: Qualitative interviews (n = 18) and two small group discussions (n = 10) were conducted with GPs. For the qualitative content analysis, we formed a system of categories based on the domains of the Theoretical Domains Framework (TDF). Results: Participants actively weighed various factors when deciding between prescribing phenprocoumon or DOACs. Costs played a subordinate role although all participants were aware that DOACs come at a higher cost than phenprocoumon. Trend reports served as a tool for GPs to assess their prescribing practices, however did not lead to a change in prescribing behaviour. The interviewees had a very heterogeneous view of safety, effect, and evidence of phenprocoumon or DOACs. The cooperation of the patients is crucial. Time is a significant challenge for participants when initiating patients on or switching them to phenprocoumon, which is especially problematic as all of the patients discharged from the hospital are put on DOACs. Conclusions: GPs are caught between economic requirements, patients’ wishes, and good collegial cooperation when deciding for or against phenprocoumon. As oral anticoagulant therapy (OAC) is mostly initiated in the hospital, and as physicians almost exclusively prescribe DOACs there, participating GPs feel overchallenged in reaching the targets set by the WSV. Trial registration number: Main ID: DRKS00019820 (German Register of Clinical Studies and World Health Organization).
CRIS-Team Scopus Importer:2025-07-25
Keywords: active substance agreement; DOACs; drug costs; VKAs; Wirkstoffvereinbarung